Association of Inducible Nitric Oxide Synthase (iNOS) Gene Diversity with Immunity Characteristics in Kampung Chicken - Muhsinin, Muhammad; Jan, Rahma; Maskur, Maskur; Rozi, Tapaul; Kasip, Lalu Muhammad; Al Farizi, Muhammad Salman (Jurnal Biologi Tropis, 2025)
The immune system of Kampung chickens is vital for maintaining health and productivity, especially in combating bacterial infections. Among the genetic components involved, the inducible nitric oxide synthase (iNOS) gene is crucial for producing nitric oxide (NO), a molecule with strong antimicrobial properties. This study investigated the association between iNOS (AluI│g.15056T>C) gene polymorphism and immune traits in Kampung chickens to enhance disease resistance. Blood samples from 100 Kampung chickens were genotyped using PCR-RFLP, and immune parameters such as leukocyte count, macrophage activity, and bacterial resistance were evaluated. Statistical analysis revealed significant differences among TT, TC, and CC genotypes. The CC genotype exhibited superior performance, including the highest macrophage activity (91.74±1.92%), activated macrophage capacity (2279.49), and bacterial death rate (60.81±3.54%). These findings suggest that the CC genotype enhances NO production, strengthening the immune response to bacterial pathogens like Staphylococcus aureus and Salmonella Pullorum. Additionally, the polymorphism contributes to improved genetic diversity and immune efficiency in Kampung chickens. The study highlights the potential of incorporating the iNOS CC genotype in selective breeding programs to produce chickens with enhanced resilience. Future research should focus on interacting environmental factors with iNOS expression to optimize its application in chicken production.